2022
DOI: 10.3389/fpls.2022.860997
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin and Flavonol Glycoside Metabolic Pathways Underpin Floral Color Mimicry and Contrast in a Sexually Deceptive Orchid

Abstract: Sexually deceptive plants secure pollination by luring specific male insects as pollinators using a combination of olfactory, visual, and morphological mimicry. Flower color is a key component to this attraction, but its chemical and genetic basis remains poorly understood. Chiloglottis trapeziformis is a sexually deceptive orchid which has predominantly dull green-red flowers except for the central black callus projecting from the labellum lamina. The callus mimics the female of the pollinator and the stark c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 127 publications
1
10
0
Order By: Relevance
“…No avone but only avonols were also detected in petals of Rhododendron, except for quercetin glycosides and kaempferol glycosides, gossypetin, myricetin, and azaleatin derivatives also existed [49]. The same phenomenon can also be seen in orchid, besides quercetin glycosides and kaempferol glycosides, isorhamnetin derivatives also existed [50]. In petals of other plants, avone and avonol usually coexist.…”
Section: Flavonols Act As Background Color In Petals Of 'Sunset Babyl...mentioning
confidence: 71%
“…No avone but only avonols were also detected in petals of Rhododendron, except for quercetin glycosides and kaempferol glycosides, gossypetin, myricetin, and azaleatin derivatives also existed [49]. The same phenomenon can also be seen in orchid, besides quercetin glycosides and kaempferol glycosides, isorhamnetin derivatives also existed [50]. In petals of other plants, avone and avonol usually coexist.…”
Section: Flavonols Act As Background Color In Petals Of 'Sunset Babyl...mentioning
confidence: 71%
“…Developmental stage and tissue-specific differential expression of genes encoding dihydroflavonol reductase, leucoanthocyanidin dioxygenase, flavonol synthase, and flavonoid O-methyltransferase that controls specific branch point into respective anthocyanin and flavonol glycoside biosynthesis (and their methylated derivatives) may also assist in maintaining the color from the earliest bud stage through to the mature flower. These findings highlight the multi-gene and regulatory complexity of the floral color adaptations involved in securing pollination by sexual deception ( Wong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 75%
“…Our study builds on this large body of prior work, and in particular on recent work on the chemical composition and genetic regulation of the temporal and spatial color patterns underpinning the visual mimicry in Chiloglottis trapeziformis ( Wong et al, 2022 ). Targeted metabolite profiling in this species revealed that the localized distribution of abundant cyanidin-based anthocyanins and diverse flavonol glycoside co-pigments give the black callus structure its distinct dark color.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the numbers of increased DAMs belonging to phenolic acids, flavonoids, lipids, terpenoids, lignans and coumarins were much lower than the decreased ones in the comparison PS5_vs_PS1, but were much higher than the increased ones in the comparison PS9_vs_PS5, suggesting that the accumulations of these kinds of metabolites are associated with the red apple ripening process. Given that they share the same biosynthesis substrates, competition occurred between anthocyanins and flavonols biosynthesis pathways in many plants (Luo et al, 2016;Zhong et al, 2020;Wong et al, 2022). For example, a comparison of anthocyanins and flavonols contents in the petals of ten Rhododendron species revealed that species with low anthocyanin contents had high flavonols (Liu et al, 2016); in Malus, competition between anthocyanins and kaempferol glycosides was found to be related to pollen tube growth and seed set (Chen et al, 2021); in bilberry, procyanidins and quercetins were identified as the major flavonoids in the early fruit ripening stage, but anthocyanins accounted for the largest fraction in the later ripening stages (Jaakola et al, 2002).…”
Section: Changes In the Accumulation Of Different Kinds Of Metabolite...mentioning
confidence: 99%
“…By using the white-flowered, flavonol accumulating Mitchell line of petunia as material, Davies et al (2003) found that overexpression both of 35SCaMV-DFR sense and/or FLS antisense transgene led to the anthocyanins production and resulted in a pink-flowered phenotype. Constitutive overexpression of FLS genes from Rosa rugosa, Prunus persica, and Petunia hybrida in tobacco all resulted in white flowers, while the heterologous overexpression of DFR genes resulted in increased anthocyanins accumulations and redder flowers (Luo et al, 2016;Wong et al, 2022). Liu et al (2019b) reported that heterologous expression of the Muscari aucheri MaFLS gene in tobacco increased NtFLS expression, but inhibited the expression of tobacco anthocyanins biosynthesis genes, such as NtDFR, NtANS and NtAN2, and reduced the pigmentation of tobacco petals.…”
Section: The Differential Expression Of Structural Genes For Flavonoi...mentioning
confidence: 99%